PENGARUH MEDIA FLIPCHART MATERI KERAJAAN SAMUDERA PASAI PADA MATA PELAJARAN SEJARAH TERHADAP HASIL BELAJAR SISWA KELAS X SMA AISYIYAH 1 PALEMBANG - Tia Rusdiana, Yusinta; Heryati, Heryati; Istiqomah, Istiqomah (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
This study aims to determine the significant effect of using flipchart learning media in history subjects on student learning outcomes. class X SMA Aisyiyah 1 Palembang Academic Year 2023/2024. The type of research is a quasi-experiment. Data Collection Techniques using Observation, Interviews, Documentation, and Tests. Data Analysis: Prerequisite Tests are divided into 2, Normality Test and Homogeneity Test, Instrument Quality Tests are divided into 2, Validity and Reliability Tests, and Hypothesis Testing. The conclusion shows the Effect of Flipchart Media in the material of the Samudera Pasai kingdom in history subjects. Based on the results of the analysis, it is known that the correlation coefficient value of history learning outcomes against flipchart media seen from the pre-test and post-test is 2.485 ≥0.05. this is proven through hypothesis testing, which shows a sig.t value of 0.000 ≤ 0.05 (significant), so that H0 is rejected and Ha is accepted. So it can be concluded that flipchart learning media has a significant effect on the learning outcomes of class X students of SMA Aisyiyah 1 Palembang with the material of the Samudera Pasai Kingdom.